2020
DOI: 10.22219/jpa.v3i2.16150
|View full text |Cite
|
Sign up to set email alerts
|

Life Skill For Women Empowerment: Patchwork For Creativity And Entrepreneurship

Abstract: The present community service highlights life skill program for women empowerment. Particularly, the current community empowerment program involves members of PKK of RT 03 RW 02 Sumbersekar, Dau Malang. There are currently 32 members in the organization that comes from different socio-economic background. In terms of entrepreneurial skills, the women in the particular organization have limited knowledge and skill in entrepreneurship. Based on the observation and confirmed with the result of interview, most of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Chaudhry and Paquibut (2021) described the characteristics of women entrepreneurs in Oman, their contribution to the economy and plans, and the challenges they faced, such as limited market access, domestic obligations that limited their online time, and a lack of social media marketing expertise. Nurbatra and Hartono (2020) indicated that the life skill program for women's empowerment positively affected creativity and women's entrepreneurship, which improved economics. Thapa Karki and Xheneti (2018) said that in order to achieve sustainable development goals (SDGs), it was widely acknowledged that women's economic empowerment through entrepreneurship is important.…”
Section: Introductionmentioning
confidence: 99%
“…Chaudhry and Paquibut (2021) described the characteristics of women entrepreneurs in Oman, their contribution to the economy and plans, and the challenges they faced, such as limited market access, domestic obligations that limited their online time, and a lack of social media marketing expertise. Nurbatra and Hartono (2020) indicated that the life skill program for women's empowerment positively affected creativity and women's entrepreneurship, which improved economics. Thapa Karki and Xheneti (2018) said that in order to achieve sustainable development goals (SDGs), it was widely acknowledged that women's economic empowerment through entrepreneurship is important.…”
Section: Introductionmentioning
confidence: 99%